Financial planning and retirement income worries in portuguese Millennials: what is the role of financial knowledge and income in the preparation for retirement - Figueiras, Christopher André Mandl (2020)
Western populations are aging with consequences for the future of public pension systems. Little research was made regarding planning for retirement in young adults, especiallyin Portugal. This study aims to understand whether Portuguese Millennials worry about the future of the pension system and to what extent Financial Knowledge and income influence planning for retirement. A survey with 180 responses suggested that Millennials in Portugal are equally worried compared to older individuals and that Financial Knowledge is not relatedto Financial Behavior. Income influencedthe level of Financial Knowledge, Financial Behavior and participation inprivate pension funds (PPR).